Gedung Sarinah sebagai Proyek Urban Branding Kekinian dari Perspektif Kuasa dan Pengetahuan - Trihanondo, Donny (Ideas Publishing, 2024)
The dynamics of the Sarinah architecture, a 1960s modernist-style architecture that is still in use, need to be investigated using Michel Foucault s postmodernism theory to reveal knowledge through its link to power. This paper aims to: (1) describe the Sarinah building architecture, (2) explore the power actors motives who have played a role in shaping Sarinah s identity, (3) analyze the power-knowledge relationship in the transformation process of Sarinah in the contemporary era. The researcher used a qualitative approach with interview, observation and literature study. According to the research findings, after the most recent rehabilitation, the Sarinah building exhibits architecture that incorporates traditional elements, which contradicts the modernist building notion of being anti-ornamental. The Sarinah building has drawn the interest of Jakarta residents through urban branding and renovation, balancing contemporary requirements with historical legacy; yet, this has also sparked criticism in the community. Finally, power players in Indonesia continue to be unconsciously impacted by Indonesia s past, particularly the era of kingdoms in the archipelago s, when it comes to the renovation of modernist buildings that meet the conditions for cultural heritage buildings.